Mosques as Bases in Scientific Flourishing Movement During the Lifetime of the Prophet (PBUH) and the Two-Rightly-Guided Caliphs - Atharizadeh, Mahmood (Issues in Social Science, 2024)
Scientific movement in Islam commenced with the revelation of the first verses of Quran to the Prophet (PBUH) when He was ordered to Read. Then his divine mission, particularly, scientific one was started. The sacred places for fulfilling his scientific mission were mosques built by him and his companions in Mecca and Medina as well as other cities throughout Islamic territory. Unlike other temples, mosques from their early establishment played numerous functions like ritual, political, social, and educational ones, hence, the Prophet (PBUH) and His companions paid most attention to teach their followers and made them familiar with Quran and Islamic sciences in sacred places, mosques. The aim of the paper is to discuss scientific activities performed in different mosques during the lifetime of the Prophet (PBUH) and the first two- Rightly-Guided Caliphs.